Effect of Substrate Morphology on the Odd-Even Effect in Hydrophobicity of Self-Assembled Monolayers - Wang, Zhengjia (Langmuir : the ACS journal of surfaces and colloids, 2016)
Surface roughness, often captured through root-mean-square roughness (Rrms), has been shown to impact the quality of self-assembled monolayers (SAMs) formed on coinage metals. Understanding the effect of roughness on hydrophobicity of SAMs, however, is complicated by the odd-even effect-a zigzag oscillation in contact angles with changes in molecular length. We recently showed that for surfaces with Rrms > 1 nm, the odd-even effect in hydrophobicity cannot be empirically observed. In this report, we compare wetting properties of SAMs on Ag and Au surfaces of different morphologies across the Rrms ∼ 1 nm limit. We prepared surfaces with comparable properties (grain sizes and Rrms) and assessed the wetting properties of resultant SAMs. Substrates with Rrms either below or above the odd-even limit were investigated. With smoother surfaces (lower Rrms), an inverted asymmetric odd-even zigzag oscillation in static contact angles (θs) was observed with change from Au to Ag. Asymmetry in odd-even oscillation in Au was attributed to a larger change in θs from odd to even number of carbons in the n-alkanethiol and vice versa for Ag. For rougher surfaces, no odd-even effect was observed; however, a gradual increase in the static contact angle was observed. Increase in the average grain sizes (>3 times larger) on rough surfaces did not lead to significant difference in the wetting properties, suggesting that surface roughness significantly dominated the nature of the SAMs. We therefore infer that the predicted roughness-dependent limit to the observation of the odd-even effect in wetting properties of n-alkanethiols cannot be overcome by creating surfaces with large grain sizes for surfaces with Rrms > 1 nm. We also observed that the differences between Au and Ag surfaces are dominated by differences in the even-numbered SAMs, but this difference vanishes with shorter molecular chain length (≤C3)